2015
DOI: 10.1177/1362361315580767
|View full text |Cite
|
Sign up to set email alerts
|

The use of eye-tracking to explore social difficulties in cognitively able students with autism spectrum disorder: A pilot investigation

Abstract: Individuals with autism spectrum disorder do not just ‘grow out of’ their early difficulties in understanding the social world. Even for those who are cognitively able, autism-related difficulties continue into adulthood. Atypicalities attending to and interpreting communicative signals from others can provide barriers to success in education, employment and relationships. In the current study, we use eye-tracking during real social interaction to explore attention to social cues (e.g. face, eyes, mouth) and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
44
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 21 publications
3
44
1
1
Order By: Relevance
“…However, even relatively mild difficulties of pragmatic understanding can have important consequences (Hanley et al, 2015;Tobin et al, 2014). If an individual repeatedly does not notice hidden insults or indirectly expressed feelings of offense, he or she probably finds it hard to follow everyday social interactions, which may have negative effects on the social functioning and well-being of the individual.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, even relatively mild difficulties of pragmatic understanding can have important consequences (Hanley et al, 2015;Tobin et al, 2014). If an individual repeatedly does not notice hidden insults or indirectly expressed feelings of offense, he or she probably finds it hard to follow everyday social interactions, which may have negative effects on the social functioning and well-being of the individual.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with ASD and their neurotypical peers differ in how they look at social features, but the group differences are not consistent across conditions (for reviews see Falck-Ytter & von Hofsten, 2011;Guillon et al, 2014). Naturalistic and complex stimuli, such as social scenes, seem to provoke differences more effectively than nonnaturalistic or relatively simple stimuli, such as isolated faces (Hanley et al, 2015;Hanley, McPhillips, Mulhern, & Riby, 2013;Speer, Cook, McMahon, & Clark, 2007). Most studies that used dynamic stimuli, as opposed to static pictures, reported group differences (Bird, Press, & Richardson, 2011;Klin, Jones, Schultz, Volkmar, & Cohen, 2002;Speer et al, 2007).…”
Section: Eye Movements In High-functioning Individuals With Asdmentioning
confidence: 99%
See 2 more Smart Citations
“…Falck-Ytter and von Hofsten (2011) have stressed that the viewing of videos places participants in the role of a passive receiver of social information and lacks interactional opportunities for participation with other people (Falck-Ytter & von Hofsten, 2011;Gobel et al 2015;Guillon et al 2014). Recent developments have A c c e p t e d M a n u s c r i p t 4 4 attempted to overcome some of these limitations using face-to-face situations in which eye movements are measured using mobile equipment; to date, only a handful of such live eye tracking studies exist (Falck-Ytter, 2015;Falck-Ytter et al 2015;Freeth et al 2013;Hanley et al 2014;Hanley et al 2015;Magrelli et al 2013;Nadig et al 2010;Noris et al 2012; Thorup et al 2016;Vabalas & Freeth, 2016).…”
mentioning
confidence: 99%